Answer:
1/∛x
Explanation
Based on the therem of power of exponents;
a^-m = 1/a^m
Given the expression
x^-1/3
On comparison, you ca see that;
a = x
m = 1/3
Substitute into the general formula;
x^-1/3 = 1/a^1/3
Also,
![a^{(1)/(x) } = \sqrt[x]{a}](https://img.qammunity.org/2022/formulas/mathematics/high-school/oc2cu8qb00alffv1yq3d3dipa7in8qd4zy.png)
Hence;
![\frac{1}{x^{(1)/(3) } } = \frac{1}{\sqrt[3]{x} }](https://img.qammunity.org/2022/formulas/mathematics/high-school/kc3v3e5qzoeo6ywxxgzzneg5pl2ilb9l6f.png)
This that the required expression is 1/∛x